Modern technical means of training as a component of the latest information technologies (Pedagogy of Higher and Secondary Education, 2012)
Lisina L. O., Tkachuk V. V. Modern technical means of training as a component of the latest information technologies.This article, based on comparing and contrasting the different ways to implement the course «Technical means learning» a new approach of teaching the course for students teaching specialties. The author proposes to divide the course into two parts: hardware and software tools training.
Keywords: technical training (TT); multimedia learning tools (MLO); information technology; digital devices; software